ANALYSIS OF IDIOMATIC EXPRESSIONS IN THE NIV TO BIMK TRANSLATION OF THE HOLY BIBLE: PSALMS - Sihombing, Nadya Yosefine Putri Halomoan; Hilman, Evert Haryanto (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This study investigates the translation of idiomatic expressions from the Psalms, focusing on their semantic range, cultural context, and theological implications. Using a descriptive qualitative method, it examines the New International Version (NIV) to the Bahasa Indonesia Masa Kini (BIMK) translation of the Holy Bible. Analytical frameworks like Venuti's domestication, Nida's dynamic equivalency, and Chesterman's semantic strategies help balance cultural context and semantic range. In this study there are 1 Translation Method and 10 Translation Procedures. The translation Method is 1 Meaning-Based Translation. While the Translation techniques are 3 sentences Dynamic Equivalency, 1 sentence Liberation Theology, 1 sentence Syntactic Strategies Theory, 1 sentence Domestication, 1 sentence Adaptation, 1 sentence Paraphrase, 1 sentence Synonymy, 1 sentence Phrase Structure Change, 1 sentence Trope Change, and 1 sentence Emphasis Change.